2011
DOI: 10.1186/1479-5868-8-9
|View full text |Cite
|
Sign up to set email alerts
|

Weight-related concerns and weight-control behaviors among overweight adolescents in Delhi, India: A cross-sectional study

Abstract: BackgroundObesity is emerging as a public health problem among adolescents in India. The aim of this study was to describe specific weight-related concerns among school-going youth in Delhi, India and to assess the prevalence of weight control behaviors, including healthy and unhealthy ones. Differences by weight status, gender, grade level, and school-type (a proxy for SES in this setting) are considered.MethodsThis study is cross-sectional by design. A sample of eighth and tenth graders (n = 1818) enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
47
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 22 publications
7
47
0
2
Order By: Relevance
“…Body image ideals in India are changing along with the economic and nutritional transition: while the results of a study from 1993 suggested that South Asian women in Britain were less likely to be dissatisfied with their body weight or describe themselves as ''too fat'' when compared with Caucasian women (Wardle et al 1993), more recent studies suggest that Indian youth are more likely to idealise a slimmer body image, at times to an unhealthy extent (Goswami et al 2012;Priya et al 2010;Stigler et al 2011;Swaminathan et al 2013). This could only partially explain the low OR of overweight/obesity in the younger age group, since socioeconomic status and media exposure have been demonstrated as important combined factors of overweight and obesity for urban populations (Gouda and Prusty 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Body image ideals in India are changing along with the economic and nutritional transition: while the results of a study from 1993 suggested that South Asian women in Britain were less likely to be dissatisfied with their body weight or describe themselves as ''too fat'' when compared with Caucasian women (Wardle et al 1993), more recent studies suggest that Indian youth are more likely to idealise a slimmer body image, at times to an unhealthy extent (Goswami et al 2012;Priya et al 2010;Stigler et al 2011;Swaminathan et al 2013). This could only partially explain the low OR of overweight/obesity in the younger age group, since socioeconomic status and media exposure have been demonstrated as important combined factors of overweight and obesity for urban populations (Gouda and Prusty 2014).…”
Section: Discussionmentioning
confidence: 99%
“…, 사회경제적 상태 [7], 실제 비만수준 및 자 신이 느끼는 비만수준이 높을수록 [17], 개인이 인지하 고 있는 주관적 체형인식이 체중조절행동을 결정하는 요인으로 알려져 있으며 [18], 자아 존중감과 비만에 대 한 두려움으로 인한 비만 스트레스 [19] …”
unclassified
“…A few studies show that Indian adolescent girls express a milder form of weight dissatisfaction with added extreme fear of fatness (35) and subsequently attempt to achieve a slim and trim body shape by following various weight-loss measures (36)(37)(38) . Therefore, it seems that unhealthy weight-related behaviours seriously affect their physical and mental abilities at this vulnerable phase of growth (39) .…”
mentioning
confidence: 99%